Risk of colorectal cancer in Parkinson’s disease: a systematic review and meta-analysis of 11 million participants - Navid Bidgoli; Mohammad Hossein Salemi; Farzaneh Hasani Sadi; Zahra Farrokhi; Sahar Abbaszadeh; Elham Foroozandeh (BMC Neurology)
Abstract Background In the last twenty years, epidemiological research has suggested a potential decreased susceptibility to cancer among individuals diagnosed with Parkinson’s disease (PD), although conflicting findings exist regarding the connection between PD and Colorectal cancer (CRC). This systematic review and meta-analysis were conducted to investigate the contemporary epidemiological data on the risk of CRC in PD. Methods A comprehensive search of the literature was conducted utilizing three databases: PubMed, Scopus, and Web of Science. We included observational studies (cross-sectional, case-control, and cohort) that examined the relationship between PD and CRC. We also analyzed data obtained from the Parkinson’s Progression Markers Initiative (PPMI) to evaluate the frequency of CRC among individuals diagnosed with PD, control participants, and PD patients carrying the LRRK2 genetic variant. Results We included 22 studies with a total of 1,3137,089 PD cases were included in our study. Our analysis demonstrated a significant relationship between PD and a reduced incidence of CRC (pooled RR = 0.80, 95% CI = 0.69–0.91). Subgroup analysis based on study design revealed a significant association in the cohort (pooled RR = 0.80, 95% CI = 0.66–0.93) and case-control studies (pooled RR = 0.77, 95% CI = 0.66–0.89). Also, sub-group analysis based on the study continent showed no significant association in North America (pooled RR = 0.83, 95% CI = 0.51–1.18, and Asia (pooled RR = 0.85, 95% CI = 0.55–1.15). However, analysis based on continents indicated significant results solely in Europe (pooled RR = 0.79, 95% CI = 0.71–0.86). PPMI analysis revealed distinct differences in CRC frequencies across the three groups (p < 0.001) with PD patients with LRRK2 genetic variant exhibited the highest frequency of colorectal cancer, followed closely by healthy subjects. Conclusion In conclusion, our study demonstrates a decreased risk of CRC in individuals with PD, suggesting an inverse association between the two diseases. Further research is warranted to elucidate the underlying mechanisms driving this correlation, paving the way for the development of targeted strategies for the prevention and management of both PD and CRC.